Estudio de caso explicativo con docentes universitarios contratados en el sector público : Explanatory case study with university teachers hired in the public sector - Rivas Huaman, Rolly Guillermo (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
The present investigation was carried out under the Qualitative Approach, analyzing the positive and negative experiences in the performance of their work as contracted teachers of a Public University. As epistemological support, the Phenomenology was taken, and the Case Study was chosen as the method, the semi-structured interview as the technique. The sampling was intentional, in which three teachers who met the inclusion and exclusion criteria participated. For data analysis, ATLAS.ti software was used. The results show that the interviewees experience positive emotions, however, they also perceive some shortcomings in institutional management.